Short dual antiplatelet therapy and dual antiplatelet therapy de-escalation after primary percutaneous intervention: For whom and how - Muthspiel, Marie; Kaufmann, Christoph C.; Burger, Achim Leo; Panzer, Benjamin; Verheugt, Freek W. A.; Huber, Kurt (Frontiers in Cardiovascular Medicine, 2022)
Dual antiplatelet therapy (DAPT) for 6–12 months, followed by lifelong aspirin monotherapy is considered an effective standard therapy for the prevention of thrombo-ischemic events in patients with acute and chronic coronary syndrome (ACS, CCS) undergoing percutaneous coronary intervention (PCI) or after a primarily conservative treatment decision. In ACS patients, the stronger P2Y12-inhibitors ticagrelor or prasugrel are recommended in combination with aspirin unless the individual bleeding risk is high and shortening of DAPT is warranted or clopidogrel is preferred. However, also in patients at low individual bleeding risk, DAPT is associated with a higher risk of bleeding. In recent years, new antithrombotic treatment strategies, such as shortening DAPT followed by early P2Y12-inhibitor monotherapy and de-escalating DAPT from potent P2Y12-inhibitors to clopidogrel by maintaining DAPT duration time, have been investigated in clinical trials and shown to reduce bleeding complications in cardiovascular high-risk patients without negative effects on ischemic events. In this review, we summarize the current knowledge and discuss its implication on future antithrombotic strategies in terms of a personalized medicine.